2020
DOI: 10.1371/journal.pone.0239339
|View full text |Cite
|
Sign up to set email alerts
|

Slit-based irrigation catheters can reduce procedure-related ischemic stroke in atrial fibrillation patients undergoing radiofrequency catheter ablation

Abstract: Open irrigation ablation catheters are now the standard in radiofrequency catheter ablation (RFCA) of atrial fibrillation (AF). Among various irrigation catheters, laser-cut slit-based irrigation system (Cool Flex and FlexAbility) has a unique design to cool the catheter tip more efficiently. We aimed to assess the safety of slit-based irrigation catheters regarding prevention of procedure-related ischemic complication in AF patients undergoing RFCA. The analysis was performed with Korea University Medicine An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…However, the clinical benefit of rhythm control therapy for AFDAS patients is still uncertain. Due to the associated risks of stroke, thromboembolism, and atrio-esophageal fistula following catheter ablation ( 11 , 12 ), there is a tendency in clinical practice to avoid prescribing rhythm control therapy for AFDAS considering the real clinical benefit and cost-effectiveness ratio ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the clinical benefit of rhythm control therapy for AFDAS patients is still uncertain. Due to the associated risks of stroke, thromboembolism, and atrio-esophageal fistula following catheter ablation ( 11 , 12 ), there is a tendency in clinical practice to avoid prescribing rhythm control therapy for AFDAS considering the real clinical benefit and cost-effectiveness ratio ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the latest iteration with a mesh‐shaped tip design has been introduced (FlexAbility™ SE, Abbott) 6,7 . Thanks to the novel tip design, the irrigation flow rate of these products has been substantially reduced from 30 to 13 mL/min while it promises a reduction in the incidence of char and thrombus formation, 5 and a recent study reported that mesh‐shaped irrigation catheters are highly effective in preventing procedure‐related ischemic complications 8 . However, the FlexAbility™ SE catheter does not have a contact force (CF) technology, which helps predict the lesion size and prevent steam pops caused by a high catheter contact with the local tissue 9–11 .…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 Thanks to the novel tip design, the irrigation flow rate of these products has been substantially reduced from 30 to 13 mL/min while it promises a reduction in the incidence of char and thrombus formation, 5 and a recent study reported that mesh‐shaped irrigation catheters are highly effective in preventing procedure‐related ischemic complications. 8 However, the FlexAbility™ SE catheter does not have a contact force (CF) technology, which helps predict the lesion size and prevent steam pops caused by a high catheter contact with the local tissue. 9 , 10 , 11 A previous study reported that the FlexAbility™ SE catheter had a high recurrence rate of atrial tachycardia after atrial fibrillation (AF) ablation and required a longer ablation time than the TactiCath™ SE catheter, because of the absence of a CF sensor.…”
Section: Introductionmentioning
confidence: 99%